The Klansman's son : my journey from white nationalism to antiracism : a memoir - Black, Derek (Abrams Press, 2024)
"Derek Black was raised to take over the white nationalist movement in the United States. Their father, Don Black, was a former Grand Wizard in the Ku Klux Klan and started Stormfront, the internet's first white supremacist website--Derek built the kids' page. David Duke, was also their close family friend and mentor. Racist hatred, though often wrapped up in respectability, was all Derek knew. Then, while in college in 2013, Derek publicly renounced white nationalism and apologized for their actions and the suffering that they had caused. The majority of their family stopped speaking to them, and they disappeared into academia, convinced that they had done so much harm that there was no place for them in public life. But in 2016, as they watched the rise of Donald Trump, they immediately recognized what they were hearing--the spread and mainstreaming of the hate they had helped cultivate--and they knew that they couldn't stay silent. This is a thoughtful, insightful, and moving account of a singular life, with important lessons for our troubled times. Derek can trace a uniquely insider account of the rise of white nationalism, and how a child indoctrinated with hate can become an anti-racist adult. Few understand the ideology, motivations, or tactics of the white nationalist movement like Derek, and few have ever made so profound a change. When coded language and creeping authoritarianism spread the ideas of white nationalists, this is an essential book with a powerful voice."--Amazon